Enhancing Community Economic Self-Reliance through Training on the Processing of Local Food-Based Chips - Basrowi; Abdur Rahman Irsyadi; Gema Ika Sari; Uli Wildan Nuryanto; Hidayatulloh; Nani Rohaeni; Muhammad Fahri Ali; Dian Novitasari; Ahmad Riadudin (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This Community Service Program (PkM) aimed to strengthen community economic self-reliance through local food-based chip processing training in the Cluster Houten KSB area, Serang City, Banten. The program addressed the issue of unemployment and limited entrepreneurial skills among community members by providing alternative opportunities for household income generation through home-based businesses utilizing local resources. Method: The program employed a participatory training approach conducted on May 18, 2026. The activities included material presentations, practical demonstrations, production assistance, and interactive discussions on business opportunities and product marketing strategies. The training focused on processing sweet potatoes, cassava, and bananas into value-added chip product. Practical Applications: The program outcomes can be applied to support the development of small-scale and home-based enterprises. The acquired knowledge and skills in product processing, packaging, and business management may assist participants in creating sustainable income sources, expanding local entrepreneurship, and promoting community-based economic development. Conclusion: The results indicated improvements in participants’ knowledge and practical skills related to chip production and small business management. Participants also showed strong enthusiasm and motivation to establish independent businesses, suggesting that the program has potential to create economic opportunities, reduce unemployment, and strengthen the local creative economy.